Assessment score for green pavement technology elements - Wan Azahar, Wan Nur Aifa (2014)
Sustainable green highway is becoming an important consideration in highway construction. To implement the concept of sustainability, a green highway rating system should be introduced in Malaysia to evaluate the green design in highways. Establishing a rating system as the determination of a score point is essential to assess the elements of a green design. Currently, there is no standardized local green highway rating system aside from the scores given to each element which varies depending on the different existing rating systems being adopted. Therefore, the main objective of this study is to determine the assessment scores by using a weighted factor approach which mainly focuses on the elements in green pavement technology. Basically, the approach was used to identify the significant elements that contribute to green technology and to provide guidance in determining the qualifying score points of these elements. The weighted values of the elements comprising pavement design life, reuse pavement, soil biotechnical engineering treatments, green techniques, cool pavement, permeable pavement and quiet pavement were generated from the agreement levels obtained from the experts through a survey. Questionnaires were developed and distributed to the 109 respondents consisting of highway experts especially from concessionaires, consultants and engineers to obtain the agreed levels of listed pavement technology elements. To obtain the weighted values, the agreement levels were analyzed using factor analysis from the Statistical Package for Social Science (SPSS) software. The results showed that the green technique and soil biotechnical engineering treatment obtained the highest score which is four and considered as the main basic elements in the implementation of green highway. This research has shown that the determination of assessment scores are important towards the development of a standardized green highway rating system in Malaysia